Few Randomized Controlled Trials in Foot and Ankle Orthopaedics Include Sociodemographic Patient Data. Issue 4 (November 2022) - Martinazzi, Brandon J.; Kirchner, Gregory; Nam, Hannah; Mansfield, Kirsten N.; Dopke, Kelly; Ptasinski, Anna; Bonaddio, Vincenzo; Koroneos, Zachary; Aynardi, Michael C.
Category: Other Introduction/Purpose: Social determinants of health play a major role in patient care. Factors such as race, education, and income have all been shown to impact patient outcomes in orthopaedic surgery. While retrospective studies are often limited by data availability, prospective randomized controlled trials (RCTs) are able to select their own patient demographics to be included in their analyses. However, the representation of sociodemographic data within RCTs regarding foot and ankle surgery is undefined. Therefore, the purpose of this study was to determine the incidence of sociodemographic data being reported in contemporary foot and ankle RCTs. Methods: RCTs within the PubMed database from 2016-2021 were searched using the search term 'Foot and Ankle Surgery.' Each article's journal of publication, year of publication, and outcome of interest were recorded. Articles were separated into the following outcomes of interest: Infection prevention, pain control, surgical outcomes, and non-operative outcomes. The full text of each article was reviewed to identify sociodemographic variables within the results or tables versus any part of the article (i.e., results or otherwise). Sociodemographic variables collected were race, ethnicity, insurance status, income, work status, and education. We then used the Fisher exact test to compare inclusion of sociodemographic data by journal, year, and outcome type. Results: A total of 34 studies across 15 different journals were included in our analysis. Of the 34 studies, 12 were grouped into operative outcomes, 11 into pain control, 7 into non-operative outcomes, and 4 into infection prevention. Race was reported in the results in 2 studies (5.9%), ethnicity in 1 (2.9%), insurance status in 0, income in 0, work status in 1 (2.9%) and education in 1 (2.9%). In any section other than the results, race was reported in 3 studies (8.8%), ethnicity in 1 (2.9%), insurance status in 3 (8.8%), income in 4 (11.8%), work status in 2 (5.9%), and education in 1 (2.9%). There was no difference found when comparing sociodemographic data to journal (p=0.127), year of publication (p=0.495), or outcome studies (p=0.439). Conclusion: The overall rate of sociodemographic data reported in foot and ankle RCTs is low. There was no difference in the reporting of sociodemographic data between journal, year of publication, or outcome of study.